Hematological manifestations of COVID-19. Issue 12 (14th October 2020) - Mina, Alain; van Besien, Koen; Platanias, Leonidas C.
Abstract: The emergence of the Coronavirus Disease −19 (COVID-19) pandemic, has had a tremendous global impact, resulting in substantial morbidity and mortality worldwide and especially in the United States, where nearly one third of the cases are located. Although involvement of the lower respiratory track accounts for most of the morbidity and mortality seen, the virus involves several organ systems and the syndrome exhibits clinical diversity with a wide range of symptoms and manifestations. The involvement of elements of the hematopoietic system is prominent in severe cases and associated with poor outcomes and mortality. Lymphopenia, leukopenia, thrombocytopenia, disseminated intravascular coagulation, and a prothrombotic state are common manifestations of COVID-19 and have important treatment and prognostic implications. Better understanding of the mechanisms of the pathophysiology of COVID-19-induced hematological abnormalities may ultimately result in better ways to treat them and decrease the associated morbidity and mortality.